Marsh benthic Foraminifera response to estuarine hydrological balance driven by climate variability over the last 2000 yr (Minho estuary, NW Portugal). Issue 2 (September 2014) - Moreno, João; Fatela, Francisco; Leorri, Eduardo; De la Rosa, José M.; Pereira, Inês; Araújo, M. Fátima; Freitas, M. Conceição; Corbett, D. Reide; Medeiros, Ana
Abstract: A high-resolution study of a marsh sedimentary sequence from the Minho estuary provides a new palaeoenvironmental reconstruction from NW Iberian based on geological proxies supported by historical and instrumental climatic records. A low-salinity tidal flat, dominated by Trochamminita salsa, Haplophragmoides spp. and Cribrostomoides spp., prevailed from AD 140–1360 (Roman Warm Period, Dark Ages, Medieval Climatic Anomaly). This sheltered environment was affected by high hydrodynamic episodes, marked by the increase in silt/clay ratio, decrease of organic matter, and poor and weakly preserved foraminiferal assemblages, suggesting enhanced river runoff. The establishment of low marsh began at AD 1380. This low-salinity environment, marked by colder and wet conditions, persisted from AD 1410–1770 (Little Ice Age), when foraminiferal density increased significantly. Haplophragmoides manilaensis and Trochamminita salsa mark the transition from low to high marsh at AD 1730. Since AD 1780 the abundances of salt marsh species ( Jadammina macrescens, Trochammina inflata ) increased, accompanied by a decrease in foraminiferal density, reflecting climate instability, when droughts alternate with severe floods. SW Europe marsh foraminifera respond to the hydrological balance, controlled by climatic variability modes (e.g., NAO) and solar activity, thus contributing to the understanding of NE Atlantic climate dynamics.